Endoscopic Versus Laparoscopic Treatment for Pancreatic Pseudocysts: A Systematic Review and Meta-analysis. Issue 6 (July 2021) - Hao, Wenzhen; Chen, Yunli; Jiang, Yu; Yang, Aiming
Abstract : Objective: The aim of the study was to evaluate the efficacy and safety of endoscopic treatment for pancreatic pseudocysts (PPCs) compared with laparoscopic treatment. Methods: The Embase, Medline, Cochrane Library, Web of Science databases, China National Knowledge Infrastructure Chinese citation database, and WANFANG database were systematically searched to identify all comparative trials investigating endoscopic versus laparoscopic treatment for PPC. The main outcome measures included treatment success rate, adverse events, recurrence rate, operation time, intraoperative blood loss, and hospital stay. Results: Six studies with 301 participants were included. The results suggested that there was no difference in rates of treatment success (odds ratio [OR], 0.90; 95% confidence interval [CI], 0.40–2.01; P = 0.79), adverse events (OR, 0.80, 95% CI, 0.38–1.70; P = 0.57), or recurrence (OR, 0.55, 95% CI, 0.22−1.40; P = 0.21) between endoscopic and laparoscopic treatments. However, the endoscopic group exhibited reduced operation time (weighted mean difference [WMD], −67.11; 95% CI, −77.27 to −56.96; P < 0.001), intraoperative blood loss (WMD, −65.23; 95% CI, −103.38 to −27.08; P < 0.001), and hospital stay (WMD, −2.45; 95% CI, −4.74 to −0.16; P = 0.04). Conclusions: Endoscopic treatment might be suitable for PPC patients.